Usage of mobile phones among flood victims in Malaysia - A.Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Wok, Saodah (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2018)
One of the worst flood disasters in Malaysian history that occurred in December 2014 had caused much damage including to lives, houses, and material possessions. Large parts of the country, mainly in the East Coast states of Kelantan, Terengganu, and Pahang were severely affected. This study was conducted to explore the use of the mobile phone during the 2014 Malaysian flood. A cross-sectional survey involving a total of 507 respondents who live in flood-affected areas was conducted to examine the use of the mobile phone and the satisfaction obtained from its usage. Being active users of the mobile phone, flood victims mainly used it to obtain information about the flood situation in their community and to communicate with close family members. Furthermore, mobile phones were used to gratify social, entertainment, and mobility needs. Findings of the study will have implications on uses and gratifications, mobile phone use, and natural disasters.